Pengaruh E-Learning Terhadap Motivasi Belajar PAI di SMKN 1 Koto Baru, Dharmasraya - Wati, Nola Nurahma; Aprison, Wedra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Students who experience repetitive conventional learning get disinterested and start doing things outside of the learning process. The utilization of e-learning is one of the things that might motivate pupils to study. Determining the degree of the